Moving Until The End Of Our Days Palliative Care through Dance Movement - Heidrun Panhofer; Jeanette MacDonald (Arteterapia)
This chapter presents some of the advantages that the work of Dance Movement Therapy (DMT) offers when working in palliative care. Via two clinical vignettes the importance of an empathetic kinaesthetic accompaniment unfolds, describing a presence and listening beyond words. The article shows how DMT offers a possibility to participate actively and constructively in order to build resilience, working with the body’s memory of the person. Accessing the body allows for contacting earlier memories, rescuing thus precious moments from a full and rich life; moments that were perhaps covered by the suffering and the pain of this last phase